3D-FBK pixel sensors with CMS readout: First test results - Obertino, M; Solano, A; Pereira, A; Alagoz, E; Andresen, J; Arndt, K; Bolla, G; Bortoletto, D; Boscardin, M; Brosius, R; Bubna, M; Dalla Betta, G; et al. (2013)
Silicon 3D detectors consist of an array of columnar electrodes of both doping types which penetrate entirely in the detector bulk, perpendicularly to the surface. They are emerging as one of the most promising technologies for innermost layers of tracking devices for the foreseen upgrades of the LHC. Until recently, properties of 3D sensors have been investigated mostly with ATLAS readout electronics. 3D pixel sensors compatible with the CMS readout were first fabricated at SINTEF (Oslo, Norway), and more recently at FBK (Trento, Italy) and CNM (Barcelona, Spain). Several sensors with different electrode configurations, bump-bonded with the CMS pixel PSI46 readout chip, were characterized in laboratory and tested at Fermilab with a proton beam of 120 GeV/c. Preliminary results of the data analysis are presented. © 2012 CERN.